2018
DOI: 10.7150/ijbs.26686
|View full text |Cite
|
Sign up to set email alerts
|

MiR-490-3p inhibits osteogenic differentiation in thoracic ligamentum flavum cells by targeting FOXO1

Abstract: Thoracic ossification of the ligamentum flavum (TOLF) is a rare heterotopic ossification of spinal ligaments, which is the major cause of thoracic spinal canal stenosis and myelopathy. In this study, the roles of miR-490-3p and forkhead box O1 (FOXO1) in osteogenesis of human thoracic ligamentum flavum cells were investigated. MiR-490-3p was found to be down-regulated during osteogenic differentiation of thoracic ligamentum flavum cells, while their overexpression inhibited osteogenic differentiation. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…MiR-490-3p Yang et al (2018b) first investigated the function of miR-490-3p in TOLF. MiR-490-3p presented downregulated expression during OLF process, and its overexpression further depressed osteogenic differentiation of ligament fibroblasts.…”
Section: Mir-615-3pmentioning
confidence: 99%
“…MiR-490-3p Yang et al (2018b) first investigated the function of miR-490-3p in TOLF. MiR-490-3p presented downregulated expression during OLF process, and its overexpression further depressed osteogenic differentiation of ligament fibroblasts.…”
Section: Mir-615-3pmentioning
confidence: 99%
“…Importantly, miR‐490 expression has also been correlated to the disease progression other than cancer (Table 2). Low miR‐490 levels were reported in atherosclerosis (Liu et al, 2019; Sun et al, 2013), chondrogenesis (Zhang et al, 2012), delayed‐type hypersensitivity (Singh et al, 2016), depression (Svenningsen et al, 2016), embryonic development (B. Xu et al, 2015), ischemia–reperfusion injury (heart; Wu et al, 2020), kidney toxicity (Marin et al, 2019), thoracic ossification of ligamentum flavum (TOLF; Yang et al, 2018) and tuberous sclerosis complex (Cai et al, 2017). Also, upregulated expression of miR‐490 was shown in coronary disease (Freedman et al, 2012), development (Xu et al, 2013), essential thrombocythemia (Tran et al, 2020), ulcerative colitis (Huang et al, 2017), dyslipidemia (Lim et al, 2016) and focal segmental glomerulosclerosis (Zhang et al, 2014).…”
Section: Status Of Mir‐490 In Other Diseasesmentioning
confidence: 99%
“…Low miR-490 levels were reported in atherosclerosis (Liu et al, 2019;Sun et al, 2013), chondrogenesis (Zhang et al, 2012), delayed-type hypersensitivity (Singh et al, 2016), depression (Svenningsen et al, 2016), embryonic development (B. , ischemia-reperfusion injury (heart; Wu et al, 2020), kidney toxicity (Marin et al, 2019), thoracic ossification of ligamentum flavum (TOLF; Yang et al, 2018) and tuberous sclerosis complex (Cai et al, 2017). Also, upregulated expression of miR-490 was shown in coronary disease (Freedman et al, 2012), development (Xu et al, 2013), essential thrombocythemia (Tran et al, 2020), ulcerative colitis (Huang et al, 2017), dyslipidemia (Lim et al, 2016) Overall, miR-490 was shown to possess a protective function in various diseases (Liu et al, 2019;Sun et al, 2013;Yang et al, 2018) whereas it was shown to promote the disease phenotype in irritable bowel syndrome and ischemia-reperfusion injury (heart; Ren et al, 2017;Wu et al, 2020). However, functional characterization of miR-490 is relatively less explored in the majority of the disease models and needs further evaluation.…”
Section: Status Of Mir-490 In Other Diseasesmentioning
confidence: 99%
“…It is generally believed that genetic and environmental factors can contribute to the occurrence and development of OLF. 7 However, its definite pathomechanism remains inadequately understood. Histologically, its pathological nature is considered as endochondral osteogenesis involving the differentiation of ligament fibroblasts into osteoblasts.…”
Section: Introductionmentioning
confidence: 99%